2020
DOI: 10.1186/s13063-020-04783-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Receptor Antibodies for Modulating the Systemic Inflammatory Response after Out-of-Hospital Cardiac Arrest (IMICA): study protocol for a double-blinded, placebo-controlled, single-center, randomized clinical trial

Abstract: Background Resuscitated out-of-hospital cardiac arrest (OHCA) patients who remain comatose at admission are at high risk of morbidity and mortality. This has been attributed to the post-cardiac arrest syndrome (PCAS) which encompasses multiple interacting components, including systemic inflammation. Elevated levels of circulating interleukin-6 (IL-6), a pro-inflammatory cytokine, is associated with worse outcomes in OHCA patients, including higher vasopressor requirements and higher mortality rates. In this st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Further in a recent phase II trial, blocking of IL-6 signalling pathway with tocilizumab, reduced systemic inflammation after cardiac arrest and showed an apparent cardioprotective effect. 192 The same reasoning applies to LQTS and Torsades de Pointes. 174,180 Finally, in high prevalence areas it reasonable to encourage compression only resuscitation and public access defibrillation of adults with OHCA for lay people, as it has already been implemented in many first responder programmes in Europe.…”
Section: Cardiac Arrestmentioning
confidence: 90%
“…Further in a recent phase II trial, blocking of IL-6 signalling pathway with tocilizumab, reduced systemic inflammation after cardiac arrest and showed an apparent cardioprotective effect. 192 The same reasoning applies to LQTS and Torsades de Pointes. 174,180 Finally, in high prevalence areas it reasonable to encourage compression only resuscitation and public access defibrillation of adults with OHCA for lay people, as it has already been implemented in many first responder programmes in Europe.…”
Section: Cardiac Arrestmentioning
confidence: 90%
“…Several compounds have been investigated in mitigating the inflammatory damage from cardiac arrest in both animal models and clinical trials. [25][26][27] These compounds may play an important role in the future for DCD HTX. Simple means to combat inflammatory damage in HTX has been investigated in porcine models comprising of hypertonic saline infusion to the donor and recipient 28,29 which showed promising results in attenuation inflammatory and ischemic damage from organ donation and transplantation; the method has, however, not been investigated in a DCD setting.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical trials used untargeted treatments, such as corticosteroids and targeted temperature management, and have had mixed efficacy on outcomes (Donnino et al, 2016; Shah and Mitra, 2021). A recent clinical trial in cardiac arrest showed that the IL-6 receptor antagonist tocilizumab reduced plasma C reactive protein levels and myocardial injury, but tocilizumab did not improve survival or neurological outcomes (Meyer et al, 2021). We did identify an IL-6 response in monocytes associated with poor neurological outcome, but we also found a strong association between other inflammatory cytokines, such as IFNγ and TNFα, and neurological injury.…”
Section: Discussionmentioning
confidence: 99%